Prevalence and Risk Factors of Superficial Fungal Infection among Patients Attending a Tertiary Care Hospital in Central Nepal - Jaishi, Vidya Laxmi; Parajuli, Ranjana; Dahal, Pragyan; Maharjan, Roshani (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Fungal infections of hair, nail, and skin are common worldwide and tend to increase. The present study was conducted to determine the prevalence of dermatomycoses, estimate the efficiency of rapid potassium hydroxide (KOH) wet-mount, and observe the hygienic status and the predisposing risk factors. Altogether 115 samples (nail = 77, skin = 30, and hair = 8) were obtained in a duration of December 2019 to June 2020 at Grande International Hospital, Nepal. The samples were examined by KOH wet-mount microscopy and further processed for culture. The dermatophyte test medium (DTM) was used to isolate dermatophytes separately. The fungal colonies obtained in SDA, SDA with cycloheximide/chloramphenicol and dermatophyte medium were subjected to lactophenol cotton blue (LPCB) reagent to study fungal morphology. The yeast colonies grown on SDA were subjected to Gram staining, germ-tube tests, and biochemical tests for identification. CHROMagar was used to distinguish different Candida species based on its pigment production in the medium. Various factors (age, sex, occupation, and hygiene condition) were analyzed which were associated with mycological infection. Out of 115 samples, the presence of fungal elements was detected in 20 samples by KOH. Nondermatophyte molds were the most isolated fungus in nails, skin, and hair, followed by yeast and dermatophytes, respectively. Dermatomycosis molds were the most common causative agents with 22 (14.7%) cases, followed by yeasts with 6 (5.21%) cases. Candida albicans was isolated from 5 (4.3%) cases, whereas Rhodotorula species accounted for a single (0.8%) case. Dermatophytes were isolated from 5 (4.3%) cases. Among them, n = 4(3.4%) cases revealed Trichophyton rubrum and Trichophyton mentagrophytes was isolated from single (0.8%) case. The most isolated nondermatophyte mold that follows criteria as a pathogen in our study was Cladosporium species 6 (25%) out of 27 total fungal isolates. Poor hygiene and sweating were found to be statistically significant (P<0.05) in fungal cases detected by both KOH and culture. Dermatophytes and nondermatophyte fungi were emerging as important causes of fungal infection. Both direct microscopy and culture followed by LPCB together were vital tools for the diagnosis of fungal infections.